The Militarization of the Belt and Road Initiative - Zanidis, Themistoklis Z. (HAPSc Policy Briefs Series, 2020)
This paper focuses on the potential militarization of the Chinese Belt and Road Initiative which is expected to change the current balance of power in the Indo-pacific Region, Africa, Central Asia, Middle East, Europe and South America. Inevitable, such an extensive and expensive investment program, which of great economic and political importance to China, is considered to be the indicator of the country’s global ambitions. Simultaneously, the military dimension of the BRI is also extremely important for China as enables it to gradually become a reliable security partner at least for developing initiative member states which do not have the resources to provide security to these infrastructures in their own territory. This is also crucial for Beijing’s competitors, the European Union and especially the United States which realize that via the BRI China will able to project military power in an extended geographical area way greater than the China Sea. Undoubtedly, for the Westerners, BRI and its potential militarization is a threat to their cohesion and global dominance.